Using mass spectrometry imaging to visualize age-related subcellular disruption - Hogan, Kelly A.; Zeidler, Julianna D.; Beasley, Heather K.; Alsaadi, Abrar I.; Alshaheeb, Abdulkareem A.; Chang, Yi-Chin; Tian, Hua; Hinton, Antentor O.; McReynolds, Melanie R. (Frontiers in Molecular Biosciences, 2023)
Metabolic homeostasis balances the production and consumption of energetic molecules to maintain active, healthy cells. Cellular stress, which disrupts metabolism and leads to the loss of cellular homeostasis, is important in age-related diseases. We focus here on the role of organelle dysfunction in age-related diseases, including the roles of energy deficiencies, mitochondrial dysfunction, endoplasmic reticulum (ER) stress, changes in metabolic flux in aging (e.g., Ca2+ and nicotinamide adenine dinucleotide), and alterations in the ER-mitochondria contact sites that regulate the trafficking of metabolites. Tools for single-cell resolution of metabolite pools and metabolic flux in animal models of aging and age-related diseases are urgently needed. High-resolution mass spectrometry imaging (MSI) provides a revolutionary approach for capturing the metabolic states of individual cells and cellular interactions without the dissociation of tissues. MSI can be a powerful tool to elucidate the role of stress-induced cellular dysfunction in aging.